Perkiraan Wujud Komputer Cerdas Masa Depan Melalui Penerapan Kecerdasan Buatan - The Houw Liong (Institut Teknologi Bandung, 2002)
The development of Artificial Intelligence shows that the future computer should be able to imitate the abilities of human brain such as to make logical inferences , pattern recognition, generalization, selforganize, associative memory, etc. To realize such abilities scientists are studying the mechanism and architecture of the brain. Based on this knowledge they build mathematical model of neurons and their architectures, so that they are able to imitate pattern recognition, generalization, self organized, etc. The brain function can be simulated and it is known as Artificial Neural Networks (ANN). Besides software, scientists can build neural chips and neural cards that can be plug on computers to function as coprocessors to solve problems that needs intelligent solutions. Logical inferences can be imitated by building inference engine and knowledge based or fuzzy rules based. Further development indicates that these can be map into ANN. The development makes it possible to build computers based on ANN. To imitate human brain it needs 1011 neurodes (artificial neurons) and 1015 synapses, and to realize it we needs to develop photonics and optical computers. The other development is the development of quantum computers which have greater abilities to simulate natures. Fuzzy logic which is used by a human being can be processed naturally by quantum bits (qubits) which can be superposed to represent fuzzy states or fuzzy statements.